Bioactive antioxidant coatings for poly(lactic acid) packaging films: polyphenols affect coating structure and their release in a food simulant. (19th July 2022) - Benbettaieb, Nasreddine; Mlaouah, Emna; Moundanga, Sylvie; Brachais, Claire‐Hélène; Kurek, Mia; Galić, Kata; Debeaufort, Frédéric
Abstract: BACKGROUND: Poly(lactic acid) (PLA) has limited uses for moist and acidic foods due to its barrier properties, which are fairly poor, and its sensitivity to moisture. RESULTS: Deposition of thin coatings based on natural biopolymers (gelatin) incorporating bioactive agents has allowed the development of active packaging materials while maintaining their biodegradability and their food contact material ability. Gelatin coatings containing two phenolic acids (tannic and gallic) have been tested. These coated PLA films displayed a reduction of the moisture permeability and a slight modification of the thermal properties of PLA. The antioxidant properties of the films and their release kinetics in a simulant medium have been studied and modelled. CONCLUSIONS: Incorporation of phenolic acids induced interactions with the gelatin that modified the structure of the network and positively affected the retention, diffusivity, and transfer rate of the bioactive compounds when coated PLA films were in contact with the liquid simulant. © 2022 Society of Chemical Industry.